A Cross-Sectional Study of Individual Learning Passion in Medical Education: Understanding Self-Development in Positive Psychology - Zhang, Shu-e; Ge, Si-ao; Tian, Jing; Li, Qing-lin; Wang, Ming-si; Wang, Xiao-he; Zhang, Meng; Zhao, Ji-yang; Yang, Li-bin; Cao, De-pin; Sun, Tao (Frontiers in Psychology, 2022)
Background Boosting the individual learning passion of medical students is a novel approach to improve their academic performance. It facilitates the medical education reform, motivating both policymakers and educators to focus on the function of positive psychology in the career development of medical students. Therefore, this study aimed (1) to assess the status of two types of learning passion; (2) to clarify the relationship between self-esteem and two types of learning passion among Chinese medical students; (3) to examine the mediating role of psychological capital (PsyCap) in the relationship between self-esteem and two types of learning passion, respectively; and (4) to identify the moderating role of professional identity in the relationship between PsyCap and two types of learning passion, respectively. Methods A cross-sectional online survey was conducted from April to June 2016 in China. A total of 1,218 valid questionnaires (effective completion rate: 67.93%) were collected from four medical schools. Results Self-esteem significantly and positively influenced medical students’ PsyCap (β = 0.637, P < 0.01) and two types of learning passion, including harmonious learning passion (β = 0.589, P < 0.01) and obsessive learning passion (β = 0.436, P < 0.01). PsyCap fully mediated the relationship (β = 0.578, P < 0.01) between self-esteem and harmonious learning passion positively, whereas it suppressed the relationship (β = 0.490, P < 0.01) between self-esteem and obsessive learning passion. Further, professional identity significantly moderated the correlation between PsyCap and harmonious learning passion (β = −0.554, P < 0.05), rather than obsessive learning passion (P > 0.05). Conclusion Two types of learning passion of medical students are positively influenced by self-esteem and PsyCap. Medical students with high-level self-esteem should possess strong PsyCap, which augments their harmonious as well as obsessive learning passion. Moreover, the positive effect of medical students’ PsyCap on harmonious learning passion is more notable among those with a lower professional identity. Finally, this study argues that strengths-based interventions of self-esteem and PsyCap are a beneficial approach for future enhancing learning passion in the domain of medical education.